Periodic event-triggered dynamic output feedback control of switched systems. (February 2019) - Ma, Guoqi; Pagilla, Prabhakar R.
Abstract: This paper considers the problem of co-design of a dynamic output feedback controller and a periodic event-triggering mechanism for control of switched systems under limited communication resources. The dynamic output feedback controller is designed to utilize quantized output measurements which can reduce the load on communication; a logarithmic quantizer model is assumed. The event-triggering mechanism is designed to detect events periodically which can significantly reduce sampling frequency and preclude the occurrence of Zeno behavior due to continuous-time sampling. The governing equations of the physical system combined with the equations of the dynamic output feedback controller and the event-triggering mechanism are formulated as a switched delay system. For the closed-loop switched delay system, sufficient conditions in terms of Linear Matrix Inequalities (LMIs) are obtained to achieve exponential stability with a prescribed L 2 − L ∞ attenuation performance with respect to an exogenous disturbance; both weighted and non-weighted performance can be achieved with the proposed approach. Tools and techniques from delay-dependent Lyapunov theory, free-weighting matrices, Singular Value Decomposition (SVD), and average dwell time for switched systems are used to obtain the main results. A synthesis procedure is provided for obtaining the dynamic output feedback controller gains, event-triggering condition parameters, and a lower bound on the average dwell time of the switching signal. Numerical simulation results on a switched boost converter circuit system are provided to evaluate the proposed design and results.